2019
DOI: 10.1039/c8ra10283j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of activated charcoal-herb extractum complex on the growth performance, immunological indices, intestinal morphology and microflora in weaning piglets

Abstract: This study was conducted to evaluate the effects of activated charcoal-herb extractum complex (CHC) on the growth performance, immunological indices, intestinal morphology and microflora in weaning piglets to determine the optimal supplemental dose. A total of 216 weaned piglets (Duroc  Landrace  Large White) with an initial body weight of 8.55 AE 1.18 kg were randomly assigned to six treatment groups; each treatment group had six pens, with six pigs per pen. The study period was 28 d. Pigs were fed a corn-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…In this study, we found that CHC showed its antioxidative effect by decreasing concentration of MDA in serum at 500 to 1000 mg kg −1 , and kidney and liver MDA at 500 mg kg −1 . A decreased concentration of MDA in the duodenum and jejunum was observed in pigs fed 500 and 1000 mg kg −1 of CHC in previous study [11]. MDA is the end product of lipid peroxidation by free radicals in vivo.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…In this study, we found that CHC showed its antioxidative effect by decreasing concentration of MDA in serum at 500 to 1000 mg kg −1 , and kidney and liver MDA at 500 mg kg −1 . A decreased concentration of MDA in the duodenum and jejunum was observed in pigs fed 500 and 1000 mg kg −1 of CHC in previous study [11]. MDA is the end product of lipid peroxidation by free radicals in vivo.…”
Section: Discussionmentioning
confidence: 65%
“…In a previous study, we found that CHC can promote growth performance, immunological indices, intestinal morphology and microflora in weaned piglets [11]. In the connect study, we further investigated CHC effects on oxidative stress that generated in weaning piglets and its effect on plasma lipid metabolism.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The reason might be that the main ingredients in FSE could improve proliferation of peripheral blood lymphocytes and intestinal permeability, so as to increase the intestinal capacity to utilize nutrients ( Hao et al., 2010 ). Previous research studies also showed similar results because herb extracts could help increase the height and width of villi and decrease duodenum crypt depth ( Iser et al., 2016 ); improve the duodenum, jejunum villus height, and ratio of villus height to crypt depth ( Wang et al., 2019 ); and therefore improve the gut development of broilers ( Cross et al., 2007 ).…”
Section: Discussionmentioning
confidence: 69%